Prognostic significance of circulating tumor DNA detection and quantification in cervical cancer: a systematic review and meta-analysis - Zhao, Xiumin; Hou, Shufu; Hao, Ruiqi; Zang, Yelei; Song, Dandan (Frontiers in Oncology, 2025)
BackgroundCirculating tumor DNA (ctDNA) is an emerging biomarker in cervical cancer, with elevated levels typically indicating a higher tumor burden. However, its prognostic value in cervical cancer patients remains debated. This meta-analysis aims to clarify the prognostic significance of ctDNA in this patient population.MethodsWe searched the PubMed, Cochrane Library, CNKI, and EMBASE databases for studies published up to September 30, 2024, to investigate the prognostic significance of ctDNA in cervical cancer patients. The outcome measures included overall survival (OS) and progression-free survival (PFS)/disease-free survival (DFS).ResultsThis analysis included 10 studies encompassing a total of 706 cervical cancer patients. Findings revealed that patients with detectable baseline ctDNA had significantly poorer OS(HR = 1.64, 95% CI = 1.45–1.86, P < 0.001) as well as worse PFS or DFS (HR = 1.42, 95% CI = 1.07–1.89, P = 0.015). Additionally, ctDNA detectability during treatment was strongly associated with poorer OS (HR = 17.22, 95% CI = 4.43–66.89, P < 0.001) and PFS/DFS (HR = 4.16, 95% CI = 2.57–6.73, P < 0.001).ConclusionsThis meta-analysis demonstrates that elevated ctDNA levels are significantly associated with poorer PFS, DFS, and OS in patients with cervical cancer. However, data regarding the association between ctDNA levels and OS are relatively limited, and the number of included studies remains small, with a potential risk of publication bias. Based on the current evidence, ctDNA shows promise as a valuable tool for pre-treatment assessment and an effective biomarker for monitoring therapeutic response and disease progression. Further large-scale, prospective studies are warranted to validate these findings and establish their reliability and clinical applicability.Systematic Review Registrationinplasy.com, identifier INPLASY2024120083.